Compound-specific δ13C and δ15N analyses of fatty acids and amino acids for discrimination of organic, pesticide-free, and conventional rice (Oryza sativa L.). (15th June 2019) - Chung, Ill-Min; Kim, Jae-Kwang; An, Yeon-Ju; Kwon, Chang; Kim, So-Yeon; Yang, Yu-Jin; Yarnes, Christopher T.; Chi, Hee-Youn; Kim, Seung-Hyun
Highlights: This work focuses on the detection of incorrect or fraudulent organic rice labeling. Compound-specific isotope analysis was employed for organic rice authentication. Best results were achieved by OPLS-DA combined with δ 13 C/δ 15 N amino acid analysis. δ 13 Clysine was identified as the greatest contributor (VIP > 1) for all OPLS-DA models. Abstract: Herein, we improve the procedure for organic rice authentication using compound-specific δ 13 C and δ 15 N analyses of fatty acids and amino acids, addressing the increasing demand for accurate methods to confirm organic authenticity. Organic rice (OR) and pesticide-free rice (PFR) featured higher values of δ 15 Nbulk than conventional rice (CR), whereas the corresponding differences between OR and PFR were insignificant. Additionally, OR, PFR, and CR could be discriminated based on some δ 13 Camino-acid and δ 15 Namino-acid values. δ 13 Cbulk was correlated with most δ 13 Cfatty-acid ( r  ≥ 0.596) values, and δ 15 Nbulk was strongly correlated with most δ 15 Namino-acid ( r  ≥ 0.834) values. The first component in the orthogonal projection to latent structure-discriminant analysis model allowed for a clear separation between OR and PFR, and good predictability ( Q 2 Y  = 0.506). Thus, the present study improves the reliability of organic authentication when bulk stable isotope ratio analysis alone is insufficient for the accurate discrimination of OR, PFR, and CR.